2005
DOI: 10.4319/lo.2005.50.3.0896
|View full text |Cite
|
Sign up to set email alerts
|

Complex interactions between the zebra mussel, Dreissena polymorpha, and the harmful phytoplankter, Microcystis aeruginosa

Abstract: We report a reversal in the sign of the herbivore-phytoplankton interaction between the zebra mussel (Dreissena polymorpha) and Microcystis aeruginosa, a harmful planktonic cyanobacterium. A pair of large-scale manipulations of mussel density in the same lake in consecutive years showed that when phosphorus concentrations were very low (mean total phosphorus), the effect of Dreissena on the biomass of M. aeruginosa was monotonically negative across the full range of sustainable mussel densities. When the enclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 40 publications
2
60
0
1
Order By: Relevance
“…However, we demonstrate how these benthic grazers, by enhancing light availability and possibly by focusing nutrients to the benthos in the littoral, enhances other undesirable effects of eutrophication, specifically, an overabundance of benthic macroalgal biomass. Other studies have similarly demonstrated that other adverse effects of nutrient enrichment, such as the frequency of (potentially toxic) cyanobacterial blooms, are not ameliorated, and perhaps even amplified, by the addition of benthic filter-feeders (Sarnelle et al 2005;Caraco et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, we demonstrate how these benthic grazers, by enhancing light availability and possibly by focusing nutrients to the benthos in the littoral, enhances other undesirable effects of eutrophication, specifically, an overabundance of benthic macroalgal biomass. Other studies have similarly demonstrated that other adverse effects of nutrient enrichment, such as the frequency of (potentially toxic) cyanobacterial blooms, are not ameliorated, and perhaps even amplified, by the addition of benthic filter-feeders (Sarnelle et al 2005;Caraco et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-one percent of the 53 genetically unique M. aeruginosa clones contained the microcystin toxin gene (mcyA). Genotypes with the toxin gene were found in all lakes, while four lakes harbored both genotypes possessing and genotypes lacking the toxin gene.The effects of grazers or nutrients on harmful phytoplankton blooms (HABs) or HAB toxins show high temporal and spatial variability (10,42,43,47,51). One source of this variation could be genetic dissimilarity among HAB populations.…”
mentioning
confidence: 99%
“…The effects of grazers or nutrients on harmful phytoplankton blooms (HABs) or HAB toxins show high temporal and spatial variability (10,42,43,47,51). One source of this variation could be genetic dissimilarity among HAB populations.…”
mentioning
confidence: 99%
“…Zebra mussels likely caused a radical change in the grazing pressure on phytoplankton and nutrient cycling in these systems, so shifts in correlations are not unexpected. Experimental work indicates that changes in these relationships differ depending on the range of TP in the system [66,67], which also helps explain differences between the responses in lower Green Bay versus less productive systems like Saginaw Bay of Lake Huron [13].…”
Section: Nutrient Conditionsmentioning
confidence: 96%
“…Correlations between TP and chlorophyll have been a standard measure of the effects of nutrients on ecosystem productivity and are used extensively for management decisions in the Great Lakes [54,64,65]. Such correlations can lose predictive ability when the underlying food web interactions change, which has been documented in both the Great Lakes as well as inland lakes [59,66]. In the inner bay of Green Bay the amount of chlorophyll per unit TP was shown to increase (but not significantly), in agreement with our results from 2006 to 2007 compared to relationships published from the 1980s [27,61] (unpublished data).…”
Section: Nutrient Conditionsmentioning
confidence: 99%